Microsponges: A Promising Novel Drug Delivery System - Naga Jyothi, K.; Dinesh Kumar, P.; Arshad, P.; Karthik, M.; Panneerselvam, T. (Journal of Drug Delivery and Therapeutics, 2019)
Microsponge is recent novel technique for control release and target specific drug delivery system. More and more developments in drug delivery systems are being integrated to optimize the efficacy and cost-effectiveness of the therapy. Microsponges are polymeric delivery system containing porous microspheres having a size range from 5 to 300µm. Microsponge Delivery System (MDS) is a unique technology for controlled drug delivery. This review article mainly deals with Microsponge drug delivery along with its method of preparation, characterization, advantages and release mechanism of MDS. Microsponges are characterized by particle size, entrapment efficacy, true density, % drug content and % yield, dissolution studies, Resiliency, compatibility studies and in-vitro studies. Wide range of applications is also preferred to develop drug with enhanced safety and efficacy.Keywords: Microsponge, Porous microspheres, Control release, Colon.